Construction Cost and Carbon Emission Computational Model for Office Buildings in Malaysia - M. A. Klufallah, Mustafa; Othman, Idris; Fadhil Nuruddin, Muhd; Faris Khamidi, Mohd (International Journal of Engineering and Technology, 2018)
A novel embodied carbon emission and construction cost computational optimization model has been developed based on evolutionary Genetic Algorithm (GA) for purpose built offices in the Malaysian construction industry. The GA evaluation was lack of implementation in addressing financial and environmental performances for construction projects in Malaysia. Therefore, the office project was evaluated through the adoption of ISO 14040 framework and evolutionary GA. The model was designed to provide alternative optimal design solutions for office buildings, which can be used at the early project planning and design stages. The assessment of embodied emissions was limited to pre-construction phase with â€œcradle to siteâ€ boundary. The model was tested statically to confirm the accuracy of the generated results. It provides an assessment model for managing carbon emission based on evaluation of environmental and financial performancesand it was validated by an application to an office building and the findingsÂ obtainedÂ suggestÂ that the it would be suitable for use in practice.Â Â